Ionic Liquids in Catalysis - Steinrück, Hans-Peter; Wasserscheid, Peter (Catalysis letters, 2015)
Ionic liquids (ILs), salts with melting points below 100 °C, represent a fascinating class of liquid materials typically characterized by an extremely low vapor pressure. Besides their application as new solvents or as electrolytes for electrochemical purposes, there are two important concepts of using ILs in catalysis: Liquid–liquid biphasic catalysis and IL thin film catalysis. Liquid–liquid biphasic catalysis enables either a very efficient manner to apply catalytic ILs, e.g. in Friedel–Crafts reactions, or to apply ionic transition metal catalyst solutions. In both cases, phase separation after reaction allows an easy separation of reaction products and catalyst re-use. One problem of liquid–liquid biphasic catalysis is mass transfer limitation. If the chemical reaction is much faster than the liquid–liquid mass transfer the latter limits the overall reaction rate. This problem is overcome in IL thin film catalysis where diffusion pathways and thus the characteristic time of diffusion are short. Here, Supported Ionic Liquid Phase (SILP) and Solid Catalyst with Ionic Liquid Layer (SCILL) are the two most important concepts. In both, a high surface area solid substrate is covered with a thin IL film, which contains either a homogeneously dissolved transition metal complex for SILP, or which modifies catalytically active surface sites at the support for SCILL. In each concept, interface phenomena play a very important role: These may concern the interface of an IL phase with an organic phase in the case of liquid–liquid biphasic catalysis. For IL thin film catalysis, the interfaces of the IL with the gas phase and with catalytic nanoparticles and/or support materials are of critical importance. It has recently been demonstrated that these interfaces and also the bulk of ILs can be investigated in great detail using surface science studies, which greatly contributed to the fundamental understanding of the catalytic properties of ILs and supported IL materials. Exemplary results concerning the IL/vacuum or IL/gas interface, the solubility and surface enrichment of dissolved metal complexes, the IL/support interface and the in situ monitoring of chemical reactions in ILs are presented. Graphical Abstract Important concepts in catalysis with ionic liquids are reviewed, including Supported Ionic Liquid Phase (SILP) and Solid Catalyst with Ionic Liquid Layer (SCILL), along with the detailed analysis of the relevant interfaces using surface science methods.